Behavioral Interventions in Schools : a Response-to-Intervention Guidebook. - Hulac, David (Taylor & Francis, 2010)
This book is a how-to manual for school mental health professionals, educators, and administrators that discusses a series of steps that can be used to proactively manage and prevent many different types of behavioral problems in a positive manner. It incorporates both the high structure and high behavioral expectations that are crucial for school success, but also describes following this structure in such a way that students feel included, important, and respected. Rather than requiring the mental health providers to investigate the research themselves and come up with a behavioral problem s.